2013
DOI: 10.15580/gjss.2013.9.100613886
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Ecotourism Carrying Capacity of Langeroud City (Case Study: Khorma Forest)

Abstract: Since the early 1970s, tourism has been mentioned as a (smoke free industry) which mostly focuses on using and development of natural and cultural resources of the countries. Outdoor recreational use of the forest provides an appropriate strategy to conserve them because outdoor recreation issue in connection with the forest has been intermingled with conservation. Depending on the properties of each area, it has taken a specific status. If tourism is left uncontrolled, in addition to destruction of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The RCC index is capable of identifying the visitors' impact in affecting the physical factors for PA management [87]. According to tourism management, the RCC value with the lowest value limits tourism operations [43,87]. The ECC index is based on the number and capacity of the existing staff in providing services to tourists, and it is the maximum number of visitors that will not disrupt the attraction and can be handled by the current staff members with the available management system [87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RCC index is capable of identifying the visitors' impact in affecting the physical factors for PA management [87]. According to tourism management, the RCC value with the lowest value limits tourism operations [43,87]. The ECC index is based on the number and capacity of the existing staff in providing services to tourists, and it is the maximum number of visitors that will not disrupt the attraction and can be handled by the current staff members with the available management system [87].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Wiyono et al [42] in the Ujung Kulon national park of Indonesia, the PCC, RCC, and ECC were estimated as 20,000, 4838, and 6 visitors per day (v/d), respectively. Amiry Lagmoj et al [43] estimated the ETCC using PCC, RCC, and ECC indices in the Khorma PA of Langeroud city, in northern Iran. The findings showed that the PCC, RCC, and ECC were estimated to be 3712, 2001, and 69 v/d, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lagmoj et al [29] in their study evaluated TCC in three ways viz., PCC, RCC, and ECC, and found that "ECC is in low range due to lack of required facilities and infrastructures as well as manpower for management and providing tourism services for tourists." They estimated the "PCC in Khorma forest as 3712 persons/day while RCC, considering limiting factors including the number of very hot days and the number of wet days, is 2001 persons/day.…”
Section: Tourism Carrying Capacity: a Review Of Conceptmentioning
confidence: 99%
“…This carrying capacity is defined as exceeding the limit when the natural destruction destroyed natural habitats for living things to survive. Kostopoulou and Kyritsis (2006), Lagmoj et al (2013), Kurhade (2013) and Rajan et al (2013) agreed all of the above mentioned are different forms of carrying capacity that have been referred to in tourism. According to Marzuki et al (2014), tourist arrivals in Kilim is considered as high and should be planned accordingly to avoid congestion.…”
Section: Tourism Carrying Capacitymentioning
confidence: 90%